Traditional and adaptive speech audiometry in single-sided deaf (SSD) subjects rehabilitated by bone conductive implants (BCI), quality of life and long-term utilization - Covelli, Edoardo; Filippi, Chiara; Lazzerini, Francesco; Tromboni, Elisabetta; Tarentini, Silvia; Pizzolante, Sofia; Forli, Francesca; Berrettini, Stefano; Bruschini, Luca (Acta oto-laryngologica, 2025)
Single-sided deafness (SSD) encompasses the presence of a profoundly deaf ear with a normal, contralateral one. Patients with SSD may have difficulty with speech intelligibility in noise and localizing sounds. This retrospective study aims to evaluate the long-term effectiveness of bone conduction implant (BCI) in a group of patients with SSD. Audiologic benefit was assessed through conventional speech audiometry and adaptive Matrix test. Impact on quality of life was evaluated with the Glasgow Benefit Inventory (GBI) questionnaire. BCI usage data were also obtained from each subject. Thirty-two patients were included. No statistically significant improvements were found at standard audiometric tests using BCI, but at Matrix test the mean SRT is reached at S/N -1.16 dB without BCI and -2.07 with BCI with a statistically significant difference ( = 0.026). The mean GBI score was 25.12, ranging from -8.3 to 47.2. Ten subjects (31%) discontinued the BCI use overtime. Benefit assessment of BCI in SSD recipients can be difficult. Adaptive audiometric test could be useful. Quality of life measures seem to suggest potential 'beyond-auditory' benefits. SSD recipients can be inconsistent users of BCI.